Evolution of over-conductivity of YВа₂Сu₃О₇-δ single crystals under the exposure of irradiation by high-energy electrons - Azarenkov, N.A.; Voyevodin, V.N.; Vovk, R.V.; Vovk, N.R.; Khadzhai, G.Ya.; Kamchatnaya, S.N. (Вопросы атомной науки и техники, 2020)
The evolution of the excess conductivity of YВа₂Сu₃О₇-δ single crystals upon electron irradiation is investigated. It was shown that electron irradiation leads to a significant expansion of the temperature range for the existence of excess conductivity, thereby narrowing the region of the linear dependence of p(Т) in the ab plane. It was found that the excess conductivity Δσ(Т) of YВа₂Сu₃О₇-δ single crystals in a wide temperature range Tf<Т<T⚹ (Тf – the transition temperature from the PG to the FP mode) is subject to exponential temperature dependence. Moreover, the description of excess conductivity using the relation Δσ ⁓ (1-Т/Т⚹)exp(Δ⚹ab/T) (Δ⚹ab – the pseudogap in ab-plane) can be interpreted in terms of the mean-field theory, where T⚹ is presented as the mean-field temperature of the transition to the PG state, and the temperature dependence of the pseudogap is satisfactorily described in the framework of the BCS-BEC crossover theory. In this case, the value of the transverse coherence length ξс(0) increases 1.4 times and the 2D-3D crossover point shifts in temperature. Досліджено еволюцію надлишкової провідності монокристалів YВа₂Сu₃О₇-δ при опроміненні електронами. Показано, що опромінення електронами призводить до значного розширення температурного інтервалу існування надлишкової провідності, тим самим, звужуючи область лінійної залежності p(Т) в ab площині. Встановлено, що надлишкова провідність Δσ(Т) монокристалів YВа₂Сu₃О₇-δ в широкому інтервалі температур Tf<Т<T⚹ підпорядковується експоненційній температурній залежності. При цьому опис надлишкової провідності за допомогою співвідношення Δσ⁓(1–Т/Т⚹)exp(Δ⚹ab/T) може бути інтерпретовано в термінах теорії середнього поля, де Т⚹ представлена, як середньополева температура переходу в ПЩ-стан, а температурна залежність псевдощілини задовільно описується в рамках теорії кросовера БКШ-БЕК. При цьому величина поперечної довжини когерентності ξс(0) збільшується в 1,4 рази, і зміщується по температурі точка 2D-3D кросовера. Исследована эволюция избыточной проводимости монокристаллов YВа₂Сu₃О₇-δ при облучении электронами. Показано, что облучение электронами приводит к значительному расширению температурного интервала существования избыточной проводимости, тем самым, сужая область линейной зависимости p(Т) в ab-плоскости. Установлено, что избыточная проводимость Δσ(Т) монокристаллов YВа₂Сu₃О₇-δ в широком интервале температур Tf<Т<T⚹ подчиняется экспоненциальной температурной зависимости. При этом описание избыточной проводимости с помощью соотношения Δσ⁓(1–Т/Т⚹)exp(Δ⚹ab/T) может быть интерпретировано в терминах теории среднего поля, где Т⚹ представлена, как среднеполевая температура перехода в ПЩ-состояние, а температурная зависимость псевдощели удовлетворительно описывается в рамках теории кроссовера БКШ-БЭК. При этом величина поперечной длины когерентности ξс(0) увеличивается в 1,4, раза и смещается по температуре точка 2D-3D кроссовера.